Factors associated with delayed arteriovenous fistula maturation in chronic kidney disease patients - Huey Tean, Kok (2015)

(untitled)
There has been an increasing trend of end stage renal disease patients requiring haemodialysis treatment worldwide. Vascular access remains the key component of haemodialysis treatment, unfortunately, the maintenance of this access remains a challenging problem. The maturity of arteriovenous fistula is influenced by variable factors such as age, presence of atherosclerosis, vascular calcification and bone mineral disease. This study is aimed to evaluate the biochemical factors that influence the vascular access, including comorbidities and the socio-demographics. This retrospective study was performed in Chronic Kidney Disease (CKD) Resource Center, Hospital Universiti Sains Malaysia between 2004 to 2014. One hundred medical records of patients underwent native arteriovenous fistula (AVF) creation were reviewed focusing on the associated factors and arteriovenous fistula maturity. Patients above 25 years old with chronic kidney disease stage 4 and above, with no previous intervention of the central vein and for first time AVF creation were included in this study. Exclusion criteria included periperal vascular disease, central venous stenosis, vascular access site deformity and vasculitic disease. Among the selected 100 subjects, 49 (49%) and 51 (51%) achieved normal and delayed maturation respectively. The mean (SD) age for normal AVF maturation was 58.51(11.27%) years, while delayed arteriovenous maturation was 57.61 (0.89%) years. Majority of the subjects were non-smoker and Malay. Among delayed AVF maturation, 27 (52.8%) were patients with diabetes mellitus and 47 (92.2%) were patients with hypertension. Calcium phosphate product was insignificantly associated with delayed AVFmaturation (p-value: 0.092); despite higher mean (SD) calcium phosphate product was observed in delayed mature AVF than normal mature AVF group. Diabetes mellitus, HbA1c and LDL were found to be associated with delayed AVF maturation with p-value < 0.05 respectively. Whereas, LDL has statistical significance at the level of multivariable analysis in delayed AVF maturation with adjusted OR of 2.67 (95% CI: 1.62, 4.40); p-value < 0.001. In conclusion, impact on AVF maturation is multifactorial. Diabetes mellitus, HbA1c and LDL were found to be associated with delayed arteriovenous fistula maturation. A Chronic Kidney Disease subject who has increasing LDL level by 1 g/dL has 2.67 times of delayed AVF maturation.